Podnikatelský záměr - Garnolová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2007)
Bakalářská práce je podnikatelský záměrem realizace vlastního podnikání v oblasti finančního zprostředkování v oblasti pojištění a investic ve spolupráci se společností ZFP akademie, a. s. Oblast, kterou se ZFP akademie, a. s. zabývá, je zvyšování finanční gramotnosti občanů prostřednictvím pravidelně pořádaných vzdělávacích seminářů a prodej produktů vybraných partnerů v rámci speciální Kombinace a možnosti využití finančních programů samospotřebitelskou metodou.

This bachelor’s thesis is focused on the business plan for an implementation of a private business in the sprehe of financial intermediation of insurance and investments in cooperation with ZFP akademie, a. s. company (hereunder the Company). The spere of the Company’s business is the increasing of financial literacy among people via the periodically held education seminars, and the sale of the products of selected partners with the scope of the Combination, and the posibility of the self-service use of the financial programs.
Business Plan
Keywords: produkt - Kombinace; marketingová strategie; analýzy; cash flow; klient; živnost; zisk; product - Combination; marketing strategy; analyses; cash flow; client; business; profit